Epidemiology of gastrointestinal nematodes in dairy cattle in farms around Gweru, Zimbabwe - Moyo, Doreen Z. (Midlands State University, 2014)
An epidemiological study of gastrointestinal nematode infections of dairy cows and calves was conducted in two farms in Gweru district from July 2004 to July 2005. Cows had low faecal egg counts during the dry and wet seasons. Calves had significantly higher faecal egg counts during the rainy season than the dry season in both farms (P<0.05). Faecal larval cultures indicated that Haemonchus , Cooperia and Trichostrongylus were the most important nematodes. Pasture larval counts were low during the dry season but increased and peaked in March coinciding with the faecal egg counts peak. Results of the study indicate that next to calves, cows are important contributors to pasture contamination. These categories of cattle would benefit from anthelmintic treatment administered at the end of the dry season and middle of the rainy season.